Implementasi Algoritma Caesar Cipher Dan Steganografi Least Significant Bit Untuk File Dokumen - Irvan Maulana Yusup; Carudin Carudin; Intan Purnamasari (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Abstract — Security and confidentiality of a file are important aspects because the owner of the file does not want the data to be known by irresponsible parties. To keep the file secret and secure there are techniques called cryptographic algorithms and steganographic algorithms. Cryptographic algorithms are a way to change the contents of the file to be incomprehensible, while steganographic algorithms are a way of inserting files that you want to keep secret with other file types such as images, sounds, or videos. One type of cryptography is Caesar Cipher and steganography is Least Significant Bit (LSB). Caesar Cipher is a way of securing and keeping the contents of a file secret by shifting letters, while the Least Significant Bit (LSB) is a method of insertion by replacing the rightmost or backmost bits. This research uses waterfall software development with the stages consist of needs analysis, system design, implementation, and testing. The program code is written in Java language and uses the Netbeans 8.2 application. The result of the research is that with 10 research materials, 5 document files (* .doc) and 5 image files (* .png), only 2 files of each research material can be processed by this software. The tests carried out included testing the functions and steganographic criteria such as Fidelity, Recoverable, and Robustness. Keywords — Algorithm, Caesar Cipher; Least Significant Bit (LSB); Netbeans;